First Line CombinAtion Therapy in the Treatment of Stage II and III Hypertension (FLASH) - Spirk, David; Noll, Sarah; Burnier, Michel; Rimoldi, Stefano; Noll, Georg; Sudano, Isabella (Frontiers in Cardiovascular Medicine, 2020)
Background: Lowering blood pressure (BP) leads to reduced risk of stroke, myocardial infarction, and cardiovascular mortality. Single-pill combination therapies may lead to better BP control than increasing the dose of monotherapies or using more drugs separately. Objectives: The aim of the present study was to investigate the real-life use and the effect of first line and replacement single pill combination therapies containing irbesartan and hydrochlorothiazide (HCTZ) on systolic BP (SBP) control rate in patients with hypertension. Methods: Overall, 780 patients with moderate or severe hypertension either untreated (289; 37%) or uncontrolled (491; 63%) with previous therapy were included in the “First Line CombinAtion Therapy in the Treatment of Stage II and III Hypertension” (FLASH) prospective Swiss national-wide cohort study. All recruited patients received single-pill antihypertensive combination therapy containing HCTZ and irbesartan. BP was measured at baseline and after 8-week follow-up according to guidelines. Results: Mean reductions in office systolic/diastolic BP (SBP/DBP) were 23.7±13.7/11.7±8.5 mmHg, with reductions of 26.9±14.1/13.0±8.8 mmHg or 21.8±13.1/11.0±8.3 mmHg when the single-pill combination of irbesartan/HCTZ was given as first line or replacement treatment, respectively (p<0.001 for difference between first line and replacement treatment in both SBP/DBP). The guidelines-recommended goals were reached in 368 (47%), 492 (63%), and 312 (40%) patients for SBP, DBP, and systolic and diastolic, respectively. The SBP control rate was higher when the combination was used as first line treatment (52% vs. 44%; p=0.043). Overall, 145 adverse events were recorded; hypotension in 12 (1.5%) cases, hypokalaemia in 9 (1.2%), and hyperkalaemia in 3 (0.4%). Conclusions: The single-pill combination of irbesartan/HCTZ was well tolerated and achieved substantial reductions in both systolic and diastolic BP. The SBP control rate was greater when the combination was prescribed as first line treatment as suggested by recent ESC/ESH guidelines.